Role of Scientific Literacy in Eradicating Superstitious Beliefs During COVID-19 Pandemic - Sonker, Priyanka; Kumar, Nagendra (SCHOOL SCIENCE, 2021)
COVID-19 is categorized as one of the most serious respiratory diseases caused by novel coronavirus. Since its first appearance in China in December 2019 as an epidemic, the disease spread rapidly across the globe, and within few months, it became a pandemic. Due to its contagious nature and non-availability of precise therapy, many people are considering it as evil. Limited public awareness about the virus structure, its life-cycle, mode of transmission and action, diagnostic strategies, therapy, etc., is fueling such people's mindset to live with their own beliefs about the disease. Lack of proper scientific knowledge about COVID-19 prompts to nurture various myths, misbeliefs, and superstitions among people. Seeding scientific temperament and awareness based on scientific knowledge is the only way to overcome such a situation. The main focus of the study is to understand the mechanism of developed misbeliefs and superstitions among people during the COVID-19 pandemic, the merits of a scientifically literate person as an informed citizen during the current pandemic, and the role of scientific literacy at the time of COVID-19 crisis.